ANALISIS KAUSALITAS EKSPOR, OUTPUT MANUFAKTUR DAN PERTUMBUHAN EKONOMI DI NEGARA ASEAN - Rany Febriyanti Ariska; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study examines the causal relationship between manufacture export, manufacture ouput and economic growth within a panel vector autoregression (PVAR) for ASEAN countries over the period 2008-2017. The results of this study indicate that the manufacture export and the manufacture output has a one-way causality relationship that is economic growth which affects the manufacture export, the manufacture output has a one-way causality relationship that is economic growth affects the manufacture output, the export and the output manufacture has no causality.